Patient-focused medicines information: General practitioners' and pharmacists' views on websites and leaflets. (April 2019) - Young, Amber; Tordoff, June; Leitch, Sharon; Smith, Alesha
Objectives: To determine how often general practitioners (GPs) and pharmacists recommend patients obtain information about their medicines via websites and to explore factors that might improve the delivery of written information about medicines to patients. Design: Cross-sectional surveys. Setting: GPs and community pharmacists in New Zealand primary care. Method: Questionnaires were developed and sent to a sample of pharmacists and GPs. Data were collected using SurveyMonkey ® and analysed to examine views about websites and leaflets informing patients about medicines. Results: In total, 143 GPs and 126 pharmacists responded. GPs and pharmacists did not routinely direct patients to medicine information websites. Most commonly, GPs did not provide medicine information leaflets due to time constraints and concerns about possibly confusing information. Both professions thought leaflets might cause patients to worry about side-effects. Pharmacists mainly withheld leaflets because the medicine has been taken previously or because leaflet indications differed to prescribed use. A summary leaflet, if available, would be the preferred option for improving leaflet provision. Conclusion: Providing digital medicine information is uncommon in New Zealand. Summarised, relevant information tailored to patient requirements might facilitate the provision of medicines information at the point of care.